2011
DOI: 10.1021/jz201484b
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Charge Photogeneration by the Dissociation of PC70BM Excitons in Polymer/Fullerene Solar Cells

Abstract: ABSTRACT:The role of PC 70 BM excitons in driving charge photogeneration in low bandgap polymer/fullerene bulk heterojunction solar cells has been studied. Both transient absorption spectroscopy (TAS) of charge generation yields in blend films as a function of excitation energies and photocurrent quantum efficiency spectra of the corresponding devices indicate that charge generation in this system results primarily from direct optical excitation of PC 70 BM. Blend composition studies of photocurrent density an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
80
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 32 publications
9
80
0
Order By: Relevance
“…Figure 1a shows the chemical structures of the donor and acceptor molecules involved, and figure 1b presents the previously reported positions of their energy levels. [28][29][30] We used well-studied donor-acceptor blends with similarly large band offsets both for the hole and the electron transfer (MDMO shows substantial optical absorption, particularly near 500 nm, in contrast to PC 60 BM. The spectra were measured for films of each material separately and later normalised to obtain a reasonable estimate of the donor and acceptor contributions to the absorption in the blend at different wavelengths.…”
Section: Main Textmentioning
confidence: 99%
“…Figure 1a shows the chemical structures of the donor and acceptor molecules involved, and figure 1b presents the previously reported positions of their energy levels. [28][29][30] We used well-studied donor-acceptor blends with similarly large band offsets both for the hole and the electron transfer (MDMO shows substantial optical absorption, particularly near 500 nm, in contrast to PC 60 BM. The spectra were measured for films of each material separately and later normalised to obtain a reasonable estimate of the donor and acceptor contributions to the absorption in the blend at different wavelengths.…”
Section: Main Textmentioning
confidence: 99%
“…Initial processes of photon absorption, intramolecular chargetransfer (ICT) exciton formation and their following dissociation/ recombination form the basis for the device operation. These early-time dynamics in pristine pushpull polymers are quite complex and include a number of competitive processes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The initial ultrafast photophysics of polymer-based bulk heterojunctions (BHJs) with fullerenes are even more complicated and depend on a number of factors such as the particular polymer structure, acceptor type, donor-acceptor phase separation known as BHJ morphology [25] etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, efficiency of the charge generation processes of these polymers in BHJs differs substantially. BTT-DPP features extremely inefficient electron transfer to [70]PCBM which is usually explained by a too low LUMO-LUMO offset of 0.1-0.3 eV [12][13][14]39]. Agreeably, this offset might be lower than the exciton binding energy -but in the PCPDTBT:PCBM system where the PCPDTBT LUMO energy is only~0.2 eV higher than that of BTT-DPP, the electron transfer is highly efficient [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the mirror process in which charges are generated by dissociation of an acceptor exciton is very efficient as well [1]. Although the importance of hole transfer was recognised only recently, the first devices functioning primarily on hole transfer have already been demonstrated [2].Charge generation processes are but one of the processes which determine the eventual efficiency of devices. For the efficiency, one of the most important parameters is the morphology of the bulk heterojunction architecture.…”
mentioning
confidence: 99%
“…It has been shown that the mirror process in which charges are generated by dissociation of an acceptor exciton is very efficient as well [1]. Although the importance of hole transfer was recognised only recently, the first devices functioning primarily on hole transfer have already been demonstrated [2].…”
mentioning
confidence: 99%